THE ROMAN-SAMNITE BORDER ALONG THE LIRIS RIVER AS A KEY FACTOR IN THE RELATIONS BETWEEN THE PARTIES IN THE SECOND HALF OF THE IV CENTURY BC - A. P. Belikov; A. I. Cherkasov (Гуманитарные и юридические исследования)
The article examines the problem of the border along the Liris as a factor that determined the confrontational nature of the Roman-Samnite relations. Special studies on this topic are still missing in both domestic and foreign historiography. However, a consistent study of the evolution of Roman-Samnite relations allows us to single out the Liris border as the main factor that determined the nature of the interaction of the parties over the course of 50 years. To confirm this thesis, we trace and analyze the main stages of the diplomatic and military solution of the territorial problem. Delimitation of spheres of influence along the Liris and the conclusion of a defensive alliance under the treaty of 354 Bc laid the foundations for further interaction between the two peoples. At the first stage in 354-343 Bc the Liris was a kind of detente factor in relations between the two sides expanding in the same direction. However, the turning point came in connection with the outbreak of the First Samnite War of 343-341 Bc, begun through the fault of Rome. In the second stage, 341-328 Bc the official nature of the relationship between the parties was determined by the peace treaty of 341 Bc, according to which a legal border was established along the Middle Liris with the concomitant refusal of the Samnites from demarcation along the Lower Liris. Despite the apparent settlement of contradictions, in fact, between the two peoples established a state of mutual mistrust, which every year acquired an increasingly pronounced character. Once again, the Liris Valley was at the center of the confrontation. All this found its expression in the diplomatic struggle of the 330s Bc, which by the beginning of the 320s Bc showed the actual superiority of the forces of Rome due to the stabilization of the militarypolitical situation near its borders, as well as due to the weakening of the Samnites after the war with Alexander of Epirus. The third stage 327-304 Bc marked the final transition of the parties to a military solution to the « Liris problem», the first step towards which, again, was made by Rome. The turning point in hostilities in 313 Bc allowed the Quirites to establish control on both sides of the Lower and Middle Liris, which was then legally enshrined in the peace treaty of 304 Bc. In the future, of course, there were still military clashes between the parties in this region, but after 304 Bc the Liris Valley ceased to play the key role in Roman-Samnite relations. The problem of the border along the Liris was finally solved in favor of Rome.